CLASSIFICATION OF PEDAGOGICAL TECHNOLOGIES IN LANGUAGE TEACHING - Shadieva Dilrabo Kurbanovna; Kulkoraeva Gulmira Halmuradovna (Bright Mind Publishing, 2025)
The article consistently describes the use of pedagogical technologies when teaching students the Russian language. The purpose of this research work is to analyze the features of pedagogical technologies and norms of the Russian language, classification of speech errors that are often found in newspapers, on television.
Keywords: Pedagogical technologies, teaching, educational, self-educational, violations of norms, speech errors, journalism, analysis, concept, linguistics.